Uroprotective and pain-relieving effect of dietary supplementation with micronized palmitoyl-glucosamine and hesperidin in a chronic model of cyclophosphamide-induced cystitis - Gugliandolo, Enrico; Franco, Gianluca Antonio; Marino, Ylenia; Peritore, Alessio Filippo; Impellizzeri, Daniela; Cordaro, Marika; Siracusa, Rosalba; Fusco, Roberta; D’Amico, Ramona; Macrì, Francesco; Di Paola, Rosanna; Cuzzocrea, Salvatore; et al. (Frontiers in Veterinary Science, 2024)
Feline idiopathic cystitis is a common, chronic-relapsing disorder of the lower urinary tract. In addition to environmental modification/enrichment, long-term and safe treatment targeting specific pathophysiological changes may be of help. In this context, effective dietary interventions hold clinical promise. The current study aimed to investigate whether a 3:1 mixture of micronized PGA and HSP could represent a novel mechanism-oriented approach to chronic cystitis management. A newly validated rat model of cyclophosphamide (CYP)induced chronic cystitis was used (40 mg/kg, three intraperitoneal injections every 3rd day). Animals were randomized to orally receive either vehicle or PGA-HSP at a low (72 + 24 mg/kg) or high (doubled) dose for 13 days, starting three days before the chronic CYP protocol, with mesna (2mercaptoethane-sulfonate) being used as a reference drug. Higher PGA-HSP dose was effective at relieving chronic visceral pain, as measured by mechanical allodynia test (von Frey test). The severity of cystitis was also significantly improved, as shown by the reduced sonographic thickening of the bladder wall, as well as the decrease in edema, bleeding and bladder to body weight ratio compared to the vehicle treated group. A significant decrease of MPO activity, MDA level and fibrosis at Masson's trichrome staining was also observed in animals administered PGA-HSP in comparison to vehicle treated ones. The CYP-induced increase in bladder mRNA expression of proinflammatory cytokines was also significantly counteracted by the study mixture. Moreover, CYPinduced bladder mast cell accumulation and releasability were significantly decreased by PGA-HSP (even at the low dose), as determined by metachromatic staining, chymase and tryptase immunostaining as well as enzyme-linked immunosorbent assay for histamine and 5hydoxytriptamine. PGA-HSP is able to block CYP-induced decrease of tight junction proteins, claudin-1 and occludin, thus preserving the urothelial bladder function. Finally, neuroinflammatory changes were investigated, showing that dietary supplementation with PGA-HSP prevented the activation of neurons and non-neuronal cells at the spinal level, and counteracted CYP-induced increase of spinal mRNA encoding for pro-inflammatory cytokines. Altogether, the present findings confirm the uroprotective and pain-relieving effect of PGA-HSP and pave the way to potential and relevant clinical applications of the study supplement in feline idiopathic cystitis.